Ultrasound-guided lumbar erector spinae plane block versus caudal block for postoperative analgesia in hip and proximal femur surgery in pediatric patients: A prospective randomized controlled study - Mahitab Rashad Mostafa; Sherif Mohamed Soaida (2022)
(3jJe GSJNOGe JbfjGJ GdJNOjQ GdehVYj Ydi fWGb hGSY aj LQGMI GdCWaGd ddhbGjI ef BdGe eG HYO GdLQGMI h jhaQ GdJhLjg HGdehLGJ ahb GdUhJjI WQjbI BefI ddMbf GdaQOj hGdJbfjGJ GdeSJeQI aj GdJNOjQ GdehVYj , hjecf Jbdjd GSJNOGe GdJNOjQ CKfGA GdYedjI hGdCOhjI GdeScfI HYO GdLQGMI(B, (3aj gPg GdOQGSI , JeJ ebGQfI aYGdjI GdeScfGJ GdeMjWI HGdLQGMI GdNGUg HGdJNOjQ GdehVYj ddYVdI GdfGUHI GdabGQ ddcJdI eY Jdc GdNGUI HGdJNOjQ GdYLRj aj LQGMI GdhQc hLQGMI YXe GdaNP aj eQVi GdCWaGd(B. (3TedJ GdJLQHI GdebGQfI GdYThGFjI SJI hSHYjf eQjkVG cGf ef GdebQQ ELQGDge dYedjGJ LQGMjI aj GdhQc aj eSJTai GdCWaGd HLGeYI GdbGgQI (B)(3CHh GdQjT(B(. (3HGdEVGaI Edi GdHjGfGJ GdOjehZQGajI , Je JSLjd GdYdGeGJ GdMjhjI hOQLGJ GdCde heOI GdcJdI hGdeScfGJ hLQYGJ GdEfbGP CKfGA GdYedjI hHYO GdLQGMI heYOd aTd GdcJdI(B. (3cGfJ GdfJjLI GdChdjI ddOQGSI gj Jbjje OQLI GdCde YfO SGYJjf HYO GdLQGMI(B. (3hdbO hLOfG aGFOI eJhGVYI ddJNOjQ GdYLRj YfO ebGQfJg HGdJNOjQ GdehVYj ddYVdI GdfGUHI GdabGQ dJScjf GdCde HYO GdLQGMI aj LQGMI GdhQc hLQGMI YXe GdaNP aj eQVi GdCWaGd(B. (3cGfJ OQLGJ GdCde HYO GdLQGMI hhbJ GdEfbGP GdChd hYOO LQYGJ GdJScjf GdEfbGPj Cbd aj GdeQVi GdPjf jJdbhf GdJNOjQ GdYLRj(B. (3heY Pdc , de jdGMX Cj GNJdGa edMhX aj eJWdHGJ GdehGO GdCajhfjI CKfGA GdYedjI Hjf GdeLehYJjf(B.s
Thesis (Ph.D)-Cairo University,2022.
Bibliography: p. 52-61.
Keywords: (3GdJNOjQs; Ultrasound